(untitled) (Web of Teachers: Inderscience Research, 2025)
Scientific researches are being conducted to improve energy efficiency and reduce consumption of traditional energy resources by improving heat supply and ventilation systems of greenhouse complexes, using renewable energy sources and optimizing heat and technical parameters.